Development of E-Module Based on Digital Flipbook Maker Containing Chemo-Entrepreneurship (CEP) Chemical Bond Material to Increase High School Student's Interest in Learning - Masita Zumna Maulida; Agus Kamaludin (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2024)
The low interest in student learning makes chemistry challenging to understand and affects expected student learning results. This research aims to develop an e-module based on a digital flipbook maker loaded with Chemo-Entrepreneurship (CEP) chemical bond material. This research is a Research and Development (R&D) type using a 4D development model. Product quality is evaluated using student responses and product quality assessment sheets. The results of the e-module assessment by material experts get an ideal percentage of 91.4% with a very good category, media experts 92% with a very good category, reviewers 91.3% with a very good category, and a positive response from students with a percentage of 93.3%. In light of the assessment results, the e-module developed can be utilized as another learning medium on chemical bond material to increase student learning interest. The results of this study imply that it can provide references for education in choosing learning media and strategies for delivering learning materials that are effective in increasing student interest. Furthermore, this can be used as a basis for further development to produce effective media and learning approaches.